Síntese, análise cristalográfica e atividade biológica de complexos com ligantes triazenidos com fragmentos orto-halofenila e para-sulfonamidafenila - Zambiazi, Priscilla Jussiane (2013)
This study shows the triazenes ligands and complexes Pd(II), K+ and Au(I) obtained from reactions of the ligands with fragments para-sulfonamidephenyl, comprising triazene ligand 1,3-bis (4 - sulfonamidephenyl) (1) and the complex {trans-Bis[1,3-bis(4-sulfonamidephenyl)triazenide-κN1]bis(pyridine-κN)palladium(II)}{tetra(pyridine-κN)palladium(II)}bis(potssium)·water (2) and for compounds containing orto-halophenyl fragments represented by [1,3-bis(2-fluorophenyl)triazenide-κN1](triphenylphosphine- κP)gold(I) (3), [1,3-bis(2-chlorinephenyl)triazenide-κN1](triphenylphosphine-κP)gold(I) (4), [1,3-bis(2-bromidephenyl)triazenide-κN1](triphenylphosphine-κP)gold(I) (5) and [1,3-bis(2-iodinephenyl)triazenide-κN1](triphenylphosphine - κP)gold(I) (6) complexes. The compounds reported were characterized by X-ray diffraction on single crystal, and their structures in solid state are formed through supramolecular arrangements via classical and non-classical hydrogen bonding, as in the case of the compounds with the sulfonamide grouping, one can observe the formation of supramolecular synthons. In complexes 4, 5 and 6 it is observed to occur interactions halogen···halogen characterized by the formation of dimeric units associated by a center of inversion, besides having geometries classified by the angle of the links formed between the halogen and carbon atoms. Compounds 1, 2, 3, 4, 5 and 6 were subjected to evaluation front of biological activity, such as plasmidial DNA cleavage studies, evaluation of cytotoxicity and antibacterial activity, showing promising results.